Effect of older age and/or ACL injury on the dose–response relationship between ambulatory load magnitude and immediate load-induced change in serum cartilage oligomeric matrix protein - Simon Herger; Corina Nüesch; Anna-Maria Liphardt; Christian Egloff; Annegret Mündermann (Journal of Sport and Health Science)
Purpose: This study aimed to assess the influence of older vs. younger age and previous anterior cruciate ligament (ACL) injury on resting serum cartilage oligomeric matrix protein (sCOMP(tpre)) concentration, on immediate load-induced sCOMP kinetics after a 30-min treadmill walking stress (∆_sCOMP(tpost)), and on the dose–response relationship between ambulatory load magnitude and ∆_sCOMP(tpost). Methods: A total of 85 participants were recruited in 4 groups (20–30 years: 24 healthy, 23 ACL-injured; 40–60 years: 23 healthy, 15 ACL-injured). Blood samples were collected immediately before and after a walking stress at 80%, 100%, or 120% bodyweight (BW) on 3 test days and analyzed for sCOMP concentration. Linear models were used to estimate the effect of age, knee status (unilateral ACL injury, 2–10 years prior), and sex on sCOMP(tpre), ∆_sCOMP(tpost), and the dose–response between ambulatory load magnitude and ∆_sCOMP(tpost). Results: We found that sCOMP(tpre) was 21% higher in older than younger participants (p < 0.001) but did not differ between ACL-injured and healthy participants (p = 0.632). Also, ∆_sCOMP(tpost) was 19% lower in older than younger participants (p = 0.030) and increased with body mass index (p < 0.001), sCOMP(tpre) (p = 0.008), and with 120%BW (p < 0.001), independent of age, ACL injury, or sex. Conclusion: Age but not prior ACL injury influences resting sCOMP and load-induced sCOMP. The dose–response relationship between ambulatory load magnitude and load-induced sCOMP changes is not affected by age, ACL injury, or sex. A better understanding of systemic sCOMP and the role of its mechanoresponse for the understanding of osteoarthritis pathophysiology and monitoring intervention efficacy may require knowledge of individual cartilage composition and tissue-level loading parameters.